Aesthetics of Color Contrast in Andalusian Poetry – Love Poetry as a Model - Okali, Najah (El Omda in Linguistics and Discourse Analysis, 2022)
This study explores the aesthetics of color contrast among Andalusian poets, focusing on love poetry as a model, since it is one of the most widespread themes in the Andalusian literary context. It also examines the openness of the poets’ chromatic imagination as a means of expressing their emotional and affective states. Furthermore, it highlights the role of Andalusia’s beautiful natural environment in providing them with rich color-related material and vocabulary that helped shape their artistic imagery. These lexical choices permeated various poetic genres and carried specific symbolic meanings for each color. The study also traces the aesthetics of color contrast in love poetry, allowing for an aesthetic appreciation that led us to cite some of the greatest and most gifted Andalusian poets, which enriched the research with numerous textual references and examples.